2009
DOI: 10.1111/j.1467-9957.2008.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Confidence Indices and Short‐term Forecasting of Consumption*

Abstract: There is growing interest in examining the short-term link between survey-based confidence indicators and real economic activity. This paper builds on previous studies to establish whether there is a short-term predictive relationship between measures of consumer confidence and actual consumption, in a range of major industrial countries. It then extends such previous analyses by assessing whether this relation has changed over time, and whether we can attribute any time-varying relation to structural developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…In conclusion, then, the empirical analysis that has been undertaken in the current paper suggests that developments in consumer sentiment do possess independent predictive content. As such, the recommendation of Al-Eyd et al (2009), that negligible attention be paid to movements in consumer sentiment in deciding upon monetary policy, would not be supported. Moreover, this study has shown that a modest refinement of the headline CCI can produce a general improvement in forecasting performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, then, the empirical analysis that has been undertaken in the current paper suggests that developments in consumer sentiment do possess independent predictive content. As such, the recommendation of Al-Eyd et al (2009), that negligible attention be paid to movements in consumer sentiment in deciding upon monetary policy, would not be supported. Moreover, this study has shown that a modest refinement of the headline CCI can produce a general improvement in forecasting performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the results that have been presented in the previous section of the , 2002-2007. In terms of the chosen form of confidence measure, the investigation which has been conducted in this paper is most closely related to the analyses of Cotsomitis and Kwan (2006), Al-Eyd et al (2009) and Jonsson and Linden (2009). Each of these earlier studies involved a consideration of data on several countries, one of which was the UK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a more recent contribution Ludvigson (2004) supports the view that there is relatively modest independent information coming from the consumer confidence index not already included in other variables. Also, according to Al-Eyd et al (2009) the relation between consumption and confidence would be unstable over time. The authors analyse European data and find very limited predictive content for the case of Italy, both in a relation between consumption and confidence, as well as considering other variables.…”
Section: Literature and Motivationmentioning
confidence: 99%
“…As consumer confidence focuses on the willingness to pay, it can provide some information not embedded in other variables. Due to the liberalisation of financial markets, however, liquidity constraints have become less binding, leading to a decline in the impact of consumer confidence on consumption (see Al Eyd et al , ).…”
Section: Consumer Confidence and Private Consumptionmentioning
confidence: 99%